Control of cell division in Saccharomyces cerevisiae by methionyl-tRNA. - Unger, M W (1976)
We suggest that two events are necessary for an asynchronous population of cells to undergo arrest in the GI phase of the cell cycle upon nutrient starvation. First, passage through GI must be prevented by a deficiency of some metabolic intermediate. Since this intermediate may act indirectly to arrest division, we designate it the "signal". We have found three conditions under which Saccharomyces cerevisiae cells arrest division in GI: sulfate starvation of a prototroph, methionine starvation of an auxotroph, or a shift of a conditional methionyl-tRNA synthetase mutant [L-methionine: tRNA Met ligase (AMP-forming), EC 6.1.1.10] to a restrictive condition. We interpret these results to indicate that the signal for sulfate starvation in S. cerevisiae is generated near the end of the sulfate assimilation pathway (at or beyond the formation of mehtionyl-tRNA). As a unifying hypothesis, we propose that the signal for all nutrients is generated at the level of protein biosynthesis.